Synthesis of conjugated polyrotaxanes. - Michels, J; O'Connell, M; Taylor, P; Wilson, J; Cacialli, F; Anderson, H (2003)
A series of conjugated polyrotaxane insulated molecular wires are synthesised by aqueous Suzuki polymerisation, using hydrophobic binding to promote threading of the cyclodextrin units. These polyrotaxanes have conjugated polymer cores based on poly(para-phenylene), polyfluorene, and poly(diphenylene-vinylene), threaded through 0.9-1.6 cyclodextrins per repeat unit. Bulky naphthalene-3,6-disulfonate endgroups prevent the macrocycles from slipping off the conjugated polymer chains. Dialysis experiments show that the cyclodextrins become unthreaded only if smaller stoppers are used. MALDI TOF mass spectra detect oligomers with up to ten threaded cyclodextrins, and reveal the presence of some defects that result for oxidative homo-coupling of boronic acids. Weight-average molecular weights were determined by analytical ultracentrifugation, demonstrating that step-growth polymerisation is efficient enough to achieve degrees of polymerisation up to approximately 20 repeat units (84 para-phenylenes). The fluorescence spectra of these polyrotaxanes indicate that the presence of the threaded cyclodextrin macrocycles reduces the flexibility of the conjugated polymer pi-systems. Both the solution and the solid-state photoluminescence quantum yields are enhanced upon threading of the conjugated polyaromatic cores through alpha- or beta-cyclodextrins, and the emission spectra of the polyrotaxanes are blue-shifted compared to the corresponding unthreaded polymers. The greater weight of the 0-0 transition in the emission spectra, as well as the smaller Stokes shift, indicate that the polyrotaxanes are more rigid than the unthreaded polymers.